2015
DOI: 10.1021/np500796f
|View full text |Cite
|
Sign up to set email alerts
|

The Quassinoid Isobrucein B Reduces Inflammatory Hyperalgesia and Cytokine Production by Post-transcriptional Modulation

Abstract: Isobrucein B (1) is a quassinoid isolated from the Amazonian medicinal plant Picrolemma sprucei. Herein we investigate the anti-inflammatory and antihyperalgesic effects of this quassinoid. Isobrucein B (1) (0.5-5 mg/kg) inhibited carrageenan-induced inflammatory hyperalgesia in mice in a dose-dependent manner. Reduced hyperalgesia was associated with reduction in both neutrophil migration and pronociceptive cytokine production. Pretreatment with 1 inhibited in vitro production/release of cytokines TNF, IL-1β,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“… 23 25 Silva et al quite recently reported that the quassinoid isobrucein B isolated from the Amazonian medicinal plant Picrolemma sprucei exerted in vivo and in vitro anti-inflammatory activity. 26 They showed that isobrucein B inhibits the release of pro-inflammatory cytokines in LPS-activated primary murine peritoneal macrophages in a concentration-dependent manner within a similar concentration range to that used in our study (0.1–10 μM). Interestingly, isobrucein B was unable to interfere with the NF-κB signaling pathway in LPS-activated RAW264.7 macrophages; the mRNA levels of the NF-κB target gene TNF also remained unaffected.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“… 23 25 Silva et al quite recently reported that the quassinoid isobrucein B isolated from the Amazonian medicinal plant Picrolemma sprucei exerted in vivo and in vitro anti-inflammatory activity. 26 They showed that isobrucein B inhibits the release of pro-inflammatory cytokines in LPS-activated primary murine peritoneal macrophages in a concentration-dependent manner within a similar concentration range to that used in our study (0.1–10 μM). Interestingly, isobrucein B was unable to interfere with the NF-κB signaling pathway in LPS-activated RAW264.7 macrophages; the mRNA levels of the NF-κB target gene TNF also remained unaffected.…”
Section: Resultssupporting
confidence: 74%
“… 15 These data suggest that 1 might act at a post-transcriptional level as reported earlier for quassinoids. 10 , 16 …”
Section: Resultsmentioning
confidence: 99%
“…RAW 264.7 macrophages were cultured and plated in 24-well plates, treated with EEP (0.1, 1, and 10 μg/mL) for 30 min and stimulated with lipopolysaccharide (LPS) (100 ng/mL) for 4 h. After that, luciferase assay reagent was added and luminescence emission was measured using a microplate reader (FlexStation 3, Molecular Devices, Sunnyvale, CA, USA) [25,26]. The results were expressed as mean ± SD of relative luminescence units (%).…”
Section: Methodsmentioning
confidence: 99%
“…Brusatol is a member of quassinoids, group of chemical compounds related to triterpenoids, which can be isolated from evergreen tropical plants of the family Simaroubaceae (genera Brucea, grown in Southeast Asia, and Picrolemma, grown in Brazil) (6,7). Brusatol and structurally related natural compounds (bruceins, isobruceins, bruceantin, bruceoside, and others) are capable of inducing a variety of biologic effects, including antimalarial, antitrypanosomal, amoebicidal, antiinflammatory, and antineoplastic activities.…”
mentioning
confidence: 99%
“…Brusatol and structurally related natural compounds (bruceins, isobruceins, bruceantin, bruceoside, and others) are capable of inducing a variety of biologic effects, including antimalarial, antitrypanosomal, amoebicidal, antiinflammatory, and antineoplastic activities. Extracts and other preparations obtained from Simaroubaceae plants are used in traditional herbal medicine to treat fever, malaria, gastropathies, and amebic dysentery (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%